2018
DOI: 10.3329/bjp.v13i1.34939
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of skin fungi in palmar arsenical keratosis

Abstract: <p class="Abstract">The aim of this study was to examine the pattern of fungi in palmar arsenical keratosis. The skin swab was taken from the five different sites (palm, dorsum, axilla, front and back of the chest) of arsenicosis patients (n=37), arsenic exposed volunteers (n=20) and healthy volunteers (n=20) of an arsenic endemic area. Fungi were cultured in the Sabouraud dextrose agar media. The skin of the healthy volunteers contained only four species of fungi: Aspergillus, Dermatophytes, Mucor and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, Aspergillus spp. was found to be predominant fungus in the palmar surface in comparison to arsenic-exposed and healthy individuals (Moitra et al, 2018). The present study also explored and found the presence of Aspergillus spp.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…On the other hand, Aspergillus spp. was found to be predominant fungus in the palmar surface in comparison to arsenic-exposed and healthy individuals (Moitra et al, 2018). The present study also explored and found the presence of Aspergillus spp.…”
Section: Discussionsupporting
confidence: 54%
“…(Pillsburry and Rebell, 1951;Roth and James, 1988;Paulino et al, 2006) were reported as the most common fungus in the skin of healthy individuals Two studies conducted at this laboratory showed S. epidermidis and Bacillus spp. as normal bacterial flora (Khalil et al, 2016) and species of Aspergillus, Dermatophytes, Mucor and Fusarium as normal fungal flora (Moitra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation